To find the product of \( i^2 (3 - i)(6 - 7i) \), we can follow these steps:
-
Calculate \( i^2 \): \[ i^2 = -1 \]
-
Calculate the product \( (3 - i)(6 - 7i) \) using the distributive property (also known as the FOIL method): \[ (3 - i)(6 - 7i) = 3 \cdot 6 + 3 \cdot (-7i) - i \cdot 6 - i \cdot (-7i) \] Simplifying each term: \[ = 18 - 21i - 6i + 7i^2 \] Since \( i^2 = -1 \): \[ 7i^2 = 7(-1) = -7 \] Therefore: \[ = 18 - 21i - 6i - 7 \] Combining like terms: \[ = 18 - 7 - 27i = 11 - 27i \]
-
Now include the \( i^2 \) we found earlier: \[ i^2 (11 - 27i) = -1(11 - 27i) = -11 + 27i \]
-
Final result: The product of \( i^2 (3 - i)(6 - 7i) \) is: \[ -11 + 27i \]
Thus, the answer is D) \(-11 + 27i\).